Social interactions and quality of life of residents in aged care facilities: A multi-methods study - Joyce Siette; Laura Dodds; Didi Surian; Mirela Prgomet; Adam Dunn; Johanna Westbrook (PLoS ONE, 2022)
Background The relationship between social contact and quality of life is well-established within the general population. However, limited data exist about the extent of social interactions in residential aged care facilities (RACFs) providing long-term accommodation and care. We aimed to record the frequency and duration of interpersonal interactions among residents in RACFs and identify the association between residents’ interpersonal interactions and quality of life (QoL). Materials and methods A multi-methods study, including time and motion observations and a QoL survey, was conducted between September 2019 to January 2020. Thirty-nine residents from six Australian RACFs were observed between 09:30–17:30 on weekdays. Observations included residents’ actions, location of the action, and who the resident was with during the action. At the end of the observation period, residents completed a QoL survey. The proportion of time residents spent on different actions, in which location, and with whom were calculated, and correlations between these factors and QoL were analysed. Results A total of 312 hours of observations were conducted. Residents spent the greatest proportion of time in their own room (45.2%, 95%CI 40.7–49.8), alone (47.9%, 95%CI 43.0–52.7) and being inactive (25.6%, 95%CI 22.5–28.7). Residents were also largely engaged in interpersonal communication (20.2%, 95%CI 17.9–22.5) and self-initiated or scheduled events (20.5%, 95%CI 18.0–23.0). Residents’ interpersonal communication was most likely to occur in the common area (29.3%, 95%CI 22.9–35.7), residents’ own room (26.7%, 95%CI 21.0–32.4) or the dining room (24.6%, 95%CI 18.9–30.2), and was most likely with another resident (54.8%, 95%CI 45.7–64.2). Quality of life scores were low (median = 0.68, IQR = 0.54–0.76). Amount of time spent with other residents was positively correlated with QoL (r = 0.39, p = 0.02), whilst amount of time spent with facility staff was negatively correlated with QoL (r = -0.45, p = 0.008). Discussion and conclusions Our findings confirm an established association between social interactions and improved QoL. Opportunities and activities which encourage residents to engage throughout the day in common facility areas can support resident wellbeing.